PENGEMBANGAN MATERI PEMANFAATAN BERBAGAI APLIKASI HANDPHONE DALAM PEMBELAJARAN - Hasna, Afra; Arlizon, Raja; ', Rosmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims arrangement of the material on the use of mobile applications in the necessary learning for high school students in terms of the clarity of the material, the material systematics, image support, adequacy of material and support for video/game. The method used in this study, which is a method of research and development (research and development). This material is validated by the supervisor 1 and 2, guidance and counseling teachers SMAN 5 Pekanbaru, and 40 graders X3 SMAN 5 Pekanbaru. This material is tested to the student with the allocation of a 3-hour lessons (3 x 45 minutes). This material consists of understanding mobile phones and applications, a variety of applications as a medium of learning, efforts to use mobile apps as a medium of learning as well as the positive and negative impacts of the use of mobile phones. The results of the development of this material indicates the quality of the material produced is at kategoi "Good", with the acquisition of a score of 4:14 for all aspects of assessment.Keyword: Material counseling, the use of mobile applications, learning